IDENTIFIKASI OLAHRAGA TRADISIONAL DI KABUPATEN SERAM BAGIAN BARAT - Rumawatine, Ztella (Porgram Studi Diluar Kampus Utama (PSDKU) Universitas Pattimura Program Studi Pendidikan Jasmani, 2021)
Traditional sports are folk games that develop in the community. Traditional sports are a cultural culture that characterizes a country. Traditional sports are experiencing a decline in the western part of the Seram Regency, where people are no longer doing traditional sports in their area but what they are doing now are modern sports. The purpose of this study was to determine the development of traditional sports in West Seram Regency. The method of this research is descriptive qualitative using observation, interviews, and documentation. The sampling technique chosen from a study was traditional leaders, communities, and village government in the four sub-districts. Among other things, West Seram District, Kairatu District, Waisala District, and West Kairatu District. The instruments used were questionnaire and interview sheets. The results showed that these traditional sports have declined due to the influence of globalization and modernization with increasingly advanced science and technology. Therefore, research on the identification of traditional sports was carried out and it was found that the development of traditional sports still exists today, because the values ​​contained in these traditional sports are very important for the development of community identity.